Analisis Pengaruh Rasio Likuiditas dan Rasio Solvabilitas terhadap Kinerja Keuangan PT Unilever Tbk Periode 2012–2021 - Asri Nurlaeni (JURNAL AKUNTANSI DAN MANAJEMEN, 2022)
The purpose of this study is to examine the financial performance of PT Unilever Indonesia Tbk during the period 2012 to 2021 based on financial ratio analysis, particularly liquidity and solvency ratios. It also aims to describe the liquidity and solvency ratios of PT Unilever Indonesia Tbk. The analytical techniques used in this study include Liquidity Ratios (current ratio and quick ratio), Solvency Ratio (debt to asset ratio), and Financial Performance (gross profit margin). The study uses data from the past ten years (2012–2021) collected through a non-probability sampling method with purposive sampling and documentation techniques using secondary data. The statistical method applied to test the hypotheses is multiple linear regression analysis with classical assumption testing. The results of this study show that, based on simultaneous testing (F-test), the three variables; Current Ratio (X1), Quick Ratio (X2), and Debt to Asset Ratio (X3); have a significant effect on Gross Profit Margin (Y), which represents the financial performance of PT Unilever Indonesia Tbk for the 2012–2021 period.